2010
DOI: 10.1111/j.1439-0426.2010.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Semen characterization and sperm structure of the Amazon tambaqui Colossoma macropomum

Abstract: Seminal features of tambaqui were evaluated after hormonal induction of spermiation with common carp pituitary extract. Seventeen adult (6.1 ± 0.9 kg, 62 ± 6 cm) males were collected from earthen ponds and transported to indoor concrete tanks. Semen was evaluated according to volume, pH, osmolality, motility, concentration, viability, sperm morphometry and morphological abnormalities. The semen of tambaqui was white and milky. The volume was 10.2 ± 5.1 mL at pH 8.0 ± 0.1, and yielded a concentration of 9.1 · 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 20 publications
1
14
0
12
Order By: Relevance
“…Reported differences may be related to induction hormonal , diet, stage of maturation, environmental conditions (e.g., temperature, salinity, and photoperiod), ATP content, enzymatic activity, hormonal regulation of spermiation, secretory activity of the sperm duct, milt contamination, stress, or a combination of these factors (CIERESZKO, 2007). The osmolality found in this study is within pattern found in the literature for this species (260-313 mOms Kg-1) (LOPES et al, 2014;MARIA et al, 2010;NASCIMENTO et al, 2010).…”
Section: Palavras-chave: Colossoma Macropomum Piaractus Brachypomussupporting
confidence: 90%
“…Reported differences may be related to induction hormonal , diet, stage of maturation, environmental conditions (e.g., temperature, salinity, and photoperiod), ATP content, enzymatic activity, hormonal regulation of spermiation, secretory activity of the sperm duct, milt contamination, stress, or a combination of these factors (CIERESZKO, 2007). The osmolality found in this study is within pattern found in the literature for this species (260-313 mOms Kg-1) (LOPES et al, 2014;MARIA et al, 2010;NASCIMENTO et al, 2010).…”
Section: Palavras-chave: Colossoma Macropomum Piaractus Brachypomussupporting
confidence: 90%
“…Sperm concentration did not significantly differ between the three samples, but were lower than those obtained by Maria et al . (, ) and Leite et al . (), who reported concentrations for C. macropomum fish as 9.1 × 109, 7.9 × 10 9 and 19.0 × 10 9 sperms mL −1 respectively.…”
Section: Discussionmentioning
confidence: 94%
“…The methods recommend, however, that the reproductive induction of C. macropomum be carried out only once during each reproductive cycle. Maria, Azevedo, Santos, Silva and Carneiro () and Maria, Azevedo, Santos and Carneiro () studied semen characteristics and Leite, Melo, Oliveira, Pinheiro, Campello, Nunes and Salmito‐Vanderley () investigated the inseminating dose of C. macropomum from only one collection during the same reproductive cycle. The challenge in this study was to use the same males more than once during the same reproductive cycle and evaluate qualitative parameters of semen using free IMAGEJ/CASA software.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, according to the results, sprinkling eugenol on the gills does not promote morphological and viability changes in the parasites. The fluorescence technique is widely used to assess sperm viability (Maria et al, 2010;Arruda et al, 2011) and protozoa studies (Davies and Stewart, 2000;Zhang et al, 2013;Song et al, 2015). Methods employing fluorescent dyes extend the possibility of a detailed structural integrity analysis of the observed organisms (Arruda et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…After gill collection, 20 monogeneans parasites on either side of the gills were separated for evaluation of motility and viability by fluorescence method adapted from Maria et al (2010). Each parasite was allocated in a well of a Kline plate with 200 uL of distilled water and 2.5 uL of SYBR-14 fluorochromes (green) and 2.5 uL propidium iodide (red), final concentrations of 250 nM SYBR-14 and 30 μM propidium iodide.…”
Section: Experiments 1: Anesthetic Sprinkling Method Viability and Pamentioning
confidence: 99%